Centralized Fiscal Spending by Supranational Unions - Jenny Simon; Justin Mattias Valasek (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study fiscal spending by supranational unions, where participation is voluntary and countries bargain over contributions to and the allocation of a central budget. We explore the link between the allocation and nations' contributions that occurs since bargaining power is endogenous, and generically causes inefficiency. Interestingly, redistribution arises endogenously, despite nations being purely self-interested. However, there exists a trade-off between increasing equality and decreasing efficiency, which becomes more severe as the centralized budget increases. We also analyze partial ex-ante commitment through alternative decision-making institutions: Both majority rule and exogenous tax rules can improve efficiency.
Keywords: H77; H87; D71; 330; supranational unions; efficiency; public goods; redistribution; federalism; legislative bargaining